Hybrid Falcon Optimization Algorithm-PID Controller Based Wind Powered Improved Bridgeless CUK Converter for Telecom Applications - Margaret Amutha, W.; Srinivasan, P. (Arabian Journal for Science and Engineering, 2025)
This paper presents a wind-powered, enhanced bridgeless AC–DC CUK converter designed for telecom tower applications, addressing key challenges such as high ripple factor, low power density, excessive switching losses, and complex converter architecture. The proposed topology combines a conventional boost converter with a bridgeless CUK converter, utilizing a wind energy source to form the improved bridgeless AC–DC CUK converter. The primary objective is to deliver a stable, reliable, efficient, and continuous DC power supply, which is critical for ensuring uninterrupted telecom tower operations. The gating signals of the converter are controlled by a PID controller, with optimization performed using the Falcon optimization algorithm (FOA) via a pulse width modulation generator. The FOA improves system performance by overcoming the typical limitations of conventional optimization techniques, such as slow convergence rates and steady-state oscillations. To ensure continuous power supply during periods of insufficient wind, a battery backup is integrated, ensuring that telecom load demand is met. The output voltage from the improved bridgeless CUK converter (IBCC) is supplied to the load, with the system operating at a power rating of 1 kW, an input voltage of 96 V, and an output voltage of − 48 V. Simulations are conducted in MATLAB/SIMULINK, covering wind characteristics, IBCC converter performance, various operational modes, and efficiency analysis. Detailed loss calculations at the component level report an overall converter efficiency of 97.6%. A prototype of the converter, rated at 1.2 kW input power and 1 kW output power, is constructed, and the simulation results are validated through experimental hardware testing.